Glycerol electro-oxidation to dihydroxyacetone on phosphorous-doped Pd/CNT nanoparticles in alkaline medium - Muhammad Sheraz, Ahmad; Singh, Sharanjit; Cheng, C. K.; Ong, Huei Ruey; Hamidah, Abdullah; Khan, Maksudur R.; Wongsakulphasatch, Suwimol (Elsevier Ltd, 2020)
In this communication report, a comparative study between P-doped Pd/CNT and bare Pd/CNT catalyst was carried out to decouple the effects of phosphorous-doping on electro-oxidation of glycerol. The initial characterization results suggested that Pd and its oxides were successfully incorporated within the pore channels of CNTs support for both catalysts by using hydrazine-assisted hydrothermal technique. The XPS results revealed that the amount of Pd2+ for bare Pd/CNT were 1.4 times higher than P-doped electrocatalysts (about 70.1% and 48.7%, respectively) which confirms that phosphorus facilitates the reduction of Pd2+ to metallic Pd (Pd0). The electrochemical results showed that the electrochemical surface area (392.22 m2 gPd−1) and current density (26 mA/cm2) for P-doped Pd/CNT catalyst were 2.84 and 1.6 times, respectively, higher than Pd/CNT catalyst. The P-doped catalyst was found to suppress the formation of carbonaceous intermediates; thus, improved the glycerol oxidation reaction. Small quantities of deep oxidation side products such as mesoxalic acid (<2%) and tartronic acid (<0.1%) were found along with the dihydroxyacetone (DHA), a major product of glycerol electro-oxidation. The best performing catalyst exhibited 1.4 folds higher DHA selectivity (90.8%) compared to the Pd/CNT.